Productivity and constraints in smallholder beef cow-calf farms in Klaten District, Central Java, Indonesia - KHARISMA IMAM ADINATA; MUKH ARIFIN; LIMBANG KUSTIAWAN NUSWANTARA; ENDANG PURBOWATI (Asian Journal of Agriculture, 2026)
Abstract. Adinata KI, Arifin M, Nuswantara LK, Purbowati E. 2026. Productivity and constraints in smallholder beef cow-calf farms in Klaten District, Central Java, Indonesia. Asian J Agric 10 (2): g100208. https://doi.org/10.13057/asianjagric/g100208. Smallholder beef cow-calf systems on Java, Indonesia, usually have very small breeding herds, making farm productivity highly vulnerable to reproductive inefficiencies and calf losses before weaning. This survey provided a snapshot of the output of weaned calves and the main challenges faced by 92 farms with 126 productive breeding cows in Klaten District, Central Java, Indonesia, from July to November 2025. Productivity was calculated as the number of weaned calves per 100 breeding cows, based on a 12-month calf-flow accounting system. The average weaned-calf productivity was 73.46 ± 69.75 calves per 100 cows per year, with a median of 50, an interquartile range of 0-100, and a range of 0-200. Among farms with at least one calf event, mean calf mortality was 9.07 ± 24.34% (median 0; range 0-100%), with more than 85% recorded no calf losses. Mean calving interval was 15.85 ± 5.80 months (range: 10-36 months), but this estimate was based on only 27 farms (28%) that were able to recall paired consecutive birth dates. None of these indicators differed significantly across breeding-cow ownership categories (P > 0.05). The main productivity constraints identified were prolonged calving interval and concentrated preweaning calf loss. These findings indicate that improving postpartum nutritional management, colostrum provision, calving supervision, and routine reproductive recording may substantially improve productivity and calf survival in smallholder beef cattle production systems in Klaten District.